Understanding the concept of Tawarruq product in Islamic Financing among ACIS students in UiTM Puncak Alam / Nor Syazwani Mohd Afandi - Mohd Afandi, Nor Syazwani (2019)
Bay al tawaruq is one of the most popular Shariah contract and one of a modern form of financing implemented in Malaysia today by Islamic financial institutions. This study aims for three objectives. First and foremost, to analyse the level of awareness of ACIS students towards the concept of tawarruq, to discuss the understanding of concept tawarruq in Islamic financing among ACIS students in UiTM Puncak Alam and lastly, to discuss the understanding of the use of tawarruq product in Islamic banking among ACIS students. In this study, the research methodology used in quantitative method. This begins with the theory-based data collection or hypothesis. Then the internal statistics will be applied. Survey was distributed where questions are modified depending on objectives of study. The survey shows the total of 165 respondents of ACIS students from different demographic profiles are selected for the purpose of this study. The result shows that majority of the respondents are not quite clear about tawarruq product. However, some recommendations can be used to improve the acknowledgement of ACIS students. In conclusion, the objectives of this study had been successfully achieved.